KATA-KATA TABU DALAM BAHASA INGGRIS DAN BAHASA TALAUD SUATU ANALISIS KONTRASTIF - TEGI, NOLANDA PANDENSOLANG (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTThis research is entitled â€œTaboo Words in English and Talaud language: A Contrastive Analysisâ€. The objectives of this research are to identify and classify the types and meaning of taboo words and analyze the differences of taboo words in English and Talaud language. This research used a descriptive method. There are three steps to finish this research. The first step was preparation, such as reading several books related to topics, such as sociolinguistic books and other sources like thesis or papers, and also the source of the English. The second step is data collection, such as collecting the data of taboo words in the English through library studies and previous researches; while in Talaud language was taken from native speakers in Desa Riung, Talaud Island. The third step is the data was analyzed using theory of Wardhaugh (1986:230) to find out the types, to find out the meaning using Leechâ€™s theory, and both language were contrasted to find out the differences using Ladoâ€™s theory. The results of this research show that taboo words found in Talaud language were classified into eight types, such as, sex, bodily function, animal, death, excretion, curse, devil, and address terms. They shows that the causes of using taboo words are to express the emotion, such as anger, happy, and surprises, to talk about sex, to joke, and to insult.Â Keywords: taboo words; English,Talaud language; contrastive analysis, sociolinguitics